The management of equity investments capital markets, equity research, investment decisions and risk management with case studies - Χωραφάς, Δημήτρης Ν. (Amsterdam ; Boston : Elsevier, 2005)
The Management of Investments is based on an extensive research project done by the author in 2003 and 2004, in the United States, England, Germany, France, Italy and Switzerland. The author outlines the rules behind the able management of investments by private individuals, banks, and institutional investors. These rules are examined within the perspective of each entity's goals and challenges. Based on research results and on his own experience, the author demonstrates that shareholder value is usually being paid lip service. As far as investment results are concerned, there are serious risks associated to leveraging, near-sighted management, obsolescence of skills and dubious deals. But there are also investment rules which, when observed, help in avoiding the slippery path which ends with investors losing their capital. To help in explaining these rules, the book outlines the way capital markets work, equity research is done, and risks associated to biases. It also pays attention to forces propelling economic growth or downturn. Growth is usually dictated by the customer, but the customer is influenced by market psychology, liquidity, volatility, and prospects of the product or financial instrument he contemplates to buy. Case studies on instruments in the book examine equities, interest rates and exchange rates. The text also analyzes the role played by hedge funds and their strategies, as well as risks associated to alternative investments. * Explains the benefits provided by sound investment management * Suggests ways and means to gain investor confidence * Includes lessons which can be learned from the market bubble of the late 1990s, the long 2000-2003 market depression and the starting recovery in 2004.
The Art of Investing: Golden Rules of Investing; The Landscape Where Professional Asset Managers and Private Investors Meet; Capital Markets and Their Players: Capital Markets and the Securities Industry; The Trading of Equities; Regulation and Operation of the Exchanges; -- Performance Criteria and Quoted Equities: -- Technical and Fundamental Analysis; Quantitative Criteria for Equity Performance; Transparency in Financial Statements and Reputational Risk; A Private Investor's Self-Protection; Execution Risk and Damage Control: Investors' Responsibility in Risk Management; Independent Equity Research and Risk Management; Volatility, Liquidity, Leverage, and Their Impact on Investments; Methods for Judging Quoted Equities; Case Studies in Investments: Case Studies on Equity Values; Parmalat: A Case Study on Leveraging Corporate Assets.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Investments; Investment analysis; Risk management; Electronic books